An Analysis of the Subjection of (Ethno) Mathematical Knowledge in the Study Plan of Brazil’s Landless Workers’ Movement - Sachs, Línlya [UNESP]; Nogueira, Amanda Araújo Coelho (Springer Nature, 2020)
The object of analysis of this text is the Study Plan developed by the Landless Workers’ Movement (MST). This is a curricular proposal intended for Middle School (children from 11 to 14 years old) in rural schools located in areas of Land Reform in the state of Paraná (Brazil). Through Foucaultian tactics, inspired by genealogy, we discussed the subjection of (ethno)mathematical knowledge present in this document, raising doubts about the naturalness, coherence, and certainty about what constitutes (and, consequently, what does not) the curriculum, with regard to mathematics. After the analysis undertaken, we indicate three situations in which there is a subjection of (ethno)mathematical knowledge in the Study Plan: with ways of counting and numbering certain cultural groups; with the creation of maps; and with methods for area calculation. In the text, we present some possibilities for a dialogue between different knowledge, showing some ethnomathematical knowledge that could be present there.
Keywords: Curriculum; Ethnomathematics; Genealogy; Landless workers’ movement; Rural education